Early Life Nutrition Research Supported by the U.S. National Institutes of Health from 2018–2020. (14th June 2022) - Landry, Matthew; Ruiz, Lyndsey; Gibbs, Kimberlea; Radtke, Marcela; Lerman, Jennifer; Vargas, Ashley
Abstract: Objectives: The Dietary Guidelines for Americans, 2020–2025 includes guidelines for pregnancy, lactation, and children from birth to age 24-months (B-24) to reflect the growing body of evidence about appropriate nutrition during the earliest stages of life. Guidelines are based on a thorough review of the existing scientific evidence by the 2020 Dietary Guidelines Advisory Committee (DGAC). The Scientific Report of the 2020 Dietary Guidelines Advisory Committee pointed to the need for additional research during these life stages. The objective of this study was to enumerate early life (pregnancy, lactation, and B-24) nutrition research needs that are already being addressed by the scientific community and to identify remaining research gaps. Methods: The 2020 DGAC Scientific Report was reviewed, and 138 research gaps relevant to early life were identified. Research gaps were consolidated into 13 topic areas. A total of 1, 632 nutrition and early life focused research projects funded by the National Institutes of Health (NIH) between 2018–2020 were manually coded using the title, abstract, and public health relevance statement available on NIH RePORTER. Projects were coded to determine if they addressed a research gap within one of the 13 research gap topic areas. The main outcome was the percentage of NIH funded (NIH) nutrition and early life focused research projects with potential to address known early life dietary guidelines research gaps. Results: Of the reviewed and coded projects, 235 (14.4%) addressed any early life nutrition research gap. Between Fiscal Years 2018 to 2020, total costs of projects addressing any gap represented only 15% of total costs for all projects reviewed. Complementary foods, breastfeeding (never versus ever), and frequency of eating were research gap areas most frequently coded as being addressed by a funded project. Iron supplementation, seafood consumption, and maternal diet food allergens were research gap areas least frequently coded as being potentially addressed by a funded project. Conclusions: This analysis highlights multiple opportunities for changes in the federal government investment in maternal and child nutrition research to support development of effective evidence-based dietary guidelines for the improvement of early life nutrition practices and overall public health. Funding Sources: None.